Determination of closest facility tsunami evacuation building using GIS Heuristic Method: A Case Study of Meuraxa District, Banda Aceh City - Liperda, Rahmad Inca; Barandika; Syahza, Bayzura; Putri Dewi, Bella; Alif Furqan, Muhammad; Rachmawati, Nur Layli (LPPMPK - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2024)
Indonesia, characterized by its susceptibility to natural calamities such as seismic activities, tsunamis, inundations, and volcanic eruptions, experienced a significant event on December 26, 2004, when a seismic event measuring 9.1 in magnitude occurred off the northern Sumatran coast, precipitating a tsunami with particularly severe repercussions in the Aceh province. The absence of preemptive measures exacerbated the catastrophe, leading to a substantial loss of lives. Subsequent to this incident, the implementation of Tsunami Evacuation Buildings (TEB) has been underway as a preventive measure against potential tsunami disasters. The construction process involves utilizing Geographic Information System (GIS) technology for mapping during evacuations. The escalating population has rendered the existing TEB facilities insufficient for evacuation purposes, necessitating the construction of additional TEB structures. The determination of TEB locations involves a location-allocation analysis, with subsequent assessment of the nearest routes conducted through closest facility analysis. Research findings indicate that the incorporation of three new TEBs has proven effective in facilitating timely evacuation during tsunamis, accommodating a population of 6,528 within a maximum duration of 22 minutes, with a maximum capacity of 11,808. However, it is noteworthy that the efficacy of these facilities is contingent upon factors such as the condition of the building's ground floor in the event of a tsunami-induced flooding, which may influence the overall capacity